Two-dimensional electronic devices modulated by the activation of donor-like states in boron nitride. Issue 35 (28th August 2020) - Aftab, Sikandar; Samiya,; Iqbal, Muhammad Waqas; Shinde, Pragati A.; Rehman, Atteq ur; Yousuf, Saqlain; Park, Sewon; Jun, Seong Chan
Abstract : A two-dimensional (2D) layered material-based p–n diode is an essential element in the modern semiconductor industry for facilitating the miniaturization and structural flexibility of devices with high efficiency for future optoelectronic and electronic applications. Abstract : A two-dimensional (2D) layered material-based p–n diode is an essential element in the modern semiconductor industry for facilitating the miniaturization and structural flexibility of devices with high efficiency for future optoelectronic and electronic applications. Planar devices constructed previously required a complicated device structure using a photoresist, as they needed to consider non-abrupt interfaces. Here, we demonstrated a WSe2 based lateral homojunction diode obtained by applying a photo-induced effect in BN/WSe2 heterostructures upon illumination via visible and deep UV light, which represents a stable and flexible charge doping technique. We have discovered that with this technique, a field-effect transistor (FET) based on p-type WSe2 is inverted to n-WSe2 so that a high electron mobility is maintained in the h-BN/n-WSe2 heterostructures. To confirm this hypothesis, we deduced the work function values of p-WSe2 and n-WSe2 FETs by conducting Kelvin probe force microscopy (KPFM) measurements, which revealed the decline of the Fermi level from 5.07 (p-WSe2 ) to 4.21 eV (n-WSe2 ). The contact potential difference (CPD) between doped and undoped junctions was found to be 165 meV. We employed ohmic metal contacts for the planar homojunction diode by utilizing an ionic liquid gate to achieve a diode rectification ratio up to ∼10 5 with n = 1. An exceptional photovoltaic performance is also observed. The presence of a built-in potential in our devices leads to an open-circuit voltage ( V oc ) and short-circuit current ( I sc ) without an external electric field. This effective doping technique is promising to advance the concept of preparing future functional devices.